METHODOLOGY OF E-LEARNING INCULCATION - Yskak A. Nabi (European Scientific Journal, ESJ, 2015)
In the article is called the gap reasons between potential and real elearning possibilities and it is indicate on the need to develop a methodology of its inculcation; is considered elements bundles of a system subsystems which are confirmed the some elementary structural junction of the three definite elements that universal logical functional dependence characterize which is called as ―triads‖. Structural model of these junctions is represented as a conventional isosceles triangle in the vertex of which is located the element, in essence balancing the internal contradictions of the other two; is shown the contradiction softening ways; the substantial components of the methodology of e-learning inculcation in the Republic of Kazakhstan are represented as a scheme and is given a brief description of the components shown in the scheme.